PENGAWASAN ORANG ASING MENURUT UNDANG-UNDANG KEIMIGRASIAN DI INDONESIA - Dani, Akhmad (Faculty of Law, University of Palembang, 2020)
The implementation of the immigration function is very important in maintaining the sovereignty of the Indonesian state. Supervision of foreigners in Indonesia is carried out by the Immigration Office based on Law Number 6 of 2011 concerning Immigration. One of the main activities of immigration is immigration control as contained in Articles 38, 39, 40, and 41 of the Immigration Law. Immigration control is carried out on Indonesian citizens and foreigners, in terms of: granting permits for Indonesian citizens and foreigners; entering and leaving the territory of Indonesia, both Indonesian citizens and foreigners; the presence of foreigners and the activities of foreigners. Problems that arise and are related to the political, economic, social and cultural aspects of society will greatly affect the stability of State security. The immigration function which regulates and supervises the presence of foreigners in Indonesia has a significant role. Obstacles in the supervision of foreigners in Indonesia include: institutional factors, namely the organization of the surveillance activities is not yet independent, immigration control is integrated with immigration investigations and immigration actions. There are also factors in the lack of regulations for administrative and operational supervision, human resources who are not able to apply an efficient and effective approach in each implementation of their main duties and functions, and the lack of facilities and infrastructure.